Social Protection and Humanitarian Assistance Nexus for Disaster Response : Lessons Learnt from Fiji's Tropical Cyclone Winston - Mansur, Aisha; Doyle, Jesse; Ivaschenko, Oleksiy (World Bank, Washington, DC, 2017)
This discussion paper presents an analysis of the humanitarian response following Tropical Cyclone (TC) Winston, and looks specifically at the role social protection played in improving disaster response and complementing the humanitarian assistance effort in Fiji. The paper also explores the changing landscape of social protections following TC Winston and documents some of the key achievements and challenges faced in the response period. Furthermore, a list of recommendations has been put together for further discussion on future disaster responsive social protection.